Ответ:
Объяснение:
2Al + 3H2SO4 = Al2(SO4)3 + 3H2
Al(0) -3e = Al(+3) 2 ок-ие
в-ль
2H(+) +2e = H2(0) 3 в-ие
ок-ль
2KMnO4 + Na2SO3 + 2KOH = 2K2MnO4 + Na2SO4 + H2O
Mn(+7) +1e = Mn(+6) 2 в-ие
S(+4) -2e = S(+6) 1 ок-ие
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
2Al + 3H2SO4 = Al2(SO4)3 + 3H2
Al(0) -3e = Al(+3) 2 ок-ие
в-ль
2H(+) +2e = H2(0) 3 в-ие
ок-ль
2KMnO4 + Na2SO3 + 2KOH = 2K2MnO4 + Na2SO4 + H2O
Mn(+7) +1e = Mn(+6) 2 в-ие
ок-ль
S(+4) -2e = S(+6) 1 ок-ие
в-ль